Scuole e città edifici per la formazione in alcuni quartieri moderni a Napoli - Fantini, Tommaso; Puleo, Anna Maria; Visconti, Federica (TeA / Teaching Architecture, 2023)
The book is about the outcomes of the three second year Architectural Design Studios of the Bachelor degree course in Science of Architecture of the Department of Architecture of the Federico II University of Naples held during the academic year 2021/22. The three ateliers took as their year theme, the construction of a school building within the modern housing quarters in the suburbs of the city of Naples. In particular, Course A - Prof. Federica Visconti - worked on Rione Luzzatti in Poggioreale and the Barra quarters (Rione d'Azeglio, Rione Cavour and Parco Azzurro), and Courses B and C - Prof. Anna Maria Puleo and Prof. Tommaso Fantini, respectively - focused only on Rione Luzzatti sharing the goal of knowing the settlement principles of the existing in order to design Spaces of Education. On the basis of these premises, the book is not limited to being a simple collection of students' projects but aspires to offer the entire academic community (and not only) an additional condition of possibility of comparison.